PENERAPAN METODE ANOVA UNTUK ANALISIS SIFAT MEKANIK KOMPOSIT SERABUT KELAPA - Junri Lasmon Marpaung; Romels C A Lumintang; Agung Sutrisno (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
Anova test is a form of statistical hypothesis testing where we draw conclusions based on data or inferential statistical groups. The null hypothesis of the Anova test is that the data is a simple random of the same population so that it has same mean and variance expectation. The aim of research is to obtain the optimum bending strength of coco fiber composite for volume fraction of 0 % fiber and 100% resin, 10% fiber and 90% resin, 20% fiber and 80%resin, 30% fiber and 70% resin, 40% fiber and 60% resin, 50% fiber and 50% resin, 60% fiber and 40% resin, 70% fiber and 30% resin with alkali treatment for two hours and without treatment, and find the result of fracture at the specimens. Based on anova analysis with error percentase 0,05 obtained F count> F crit so that answer hypothesis to fiber treatment affect mechanical properties of bending strength F = 7.752752499 F crit = 2.657197 without treatment. Keywords : Anova Test Methods, Analysis Of Composite Mechanical Properties, CoconutFibers.